2014
DOI: 10.1002/phar.1397
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib‐Associated Tumor Lysis Syndrome

Abstract: Multiple myeloma is the second most common type of hematologic malignancy. It is a B-cell malignancy that affects the bone marrow and often results in thrombocytopenia as well as renal dysfunction. Treatment options range from oral and intravenous chemotherapy to bone marrow transplantation and supportive care. Carfilzomib was approved by the U.S. Food and Drug Administration in 2012 as a treatment option for patients with refractory multiple myeloma who have received at least two previous therapies and have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Although acute renal failure occurred in 4.2% of patients undergoing carfilzomib treatment for myeloma in an integrated safety analysis , carfilzomib proved to be safe in patients with myeloma with renal impairment, and was well tolerated and demonstrated promising efficacy . Moreover, acute renal failure and tumour lysis syndrome, described within case reports of individual patients undergoing carfilzomib‐based therapy, were well manageable if properly monitored .…”
Section: Discussionmentioning
confidence: 99%
“…Although acute renal failure occurred in 4.2% of patients undergoing carfilzomib treatment for myeloma in an integrated safety analysis , carfilzomib proved to be safe in patients with myeloma with renal impairment, and was well tolerated and demonstrated promising efficacy . Moreover, acute renal failure and tumour lysis syndrome, described within case reports of individual patients undergoing carfilzomib‐based therapy, were well manageable if properly monitored .…”
Section: Discussionmentioning
confidence: 99%
“… 1 Most of the cases of AKI in this phase II trial were attributed to carfilzomib, as no other precipitating cause could be identified; however, the mechanism of AKI was not determined. There have also been a number of case reports 2 , 3 , 4 , 5 , 6 , 7 attributing AKI to carfilzomib, some suggesting that thrombotic microangiopathy may have been the mechanism of injury based on clinical presentation and evidence from kidney biopsies, but definitive causality was not established. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…There have been several case reports providing evidence of AKI secondary to carfilzomib. 2 , 3 , 4 , 5 , 6 , 7 Two recent reports describe thrombotic microangiopathy associated with carfilzomib administration, although causality was not definitively established. 4 , 5 To our knowledge this is the first case report of biopsy-proven acute tubular necrosis (ATN) in a patient with multiple myeloma who was treated with carfilzomib.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of the kidney adverse effects were mild, progressive kidney disease was reported in 3.8% of patients, leading to discontinuation of the drug in two patients (22). There are now additional cases of AKI from carfilzomib reported in the literature (23)(24)(25)(26)(27). The possible mechanisms listed are diverse and summarized in Table 2.…”
Section: Carfilzomibmentioning
confidence: 99%
“…The possible mechanisms listed are diverse and summarized in Table 2. They range from prerenal insults, tumor lysis-like phenomenon, to biopsy-proven TMA (23)(24)(25)(26). In the initial two cases (23,24), AKI was transient and was clinically consistent with a 'prerenal' insult.…”
Section: Carfilzomibmentioning
confidence: 99%